Lobbying practices in Israel's advocacy groups. (17th December 2018) - Mano, Rita
Abstract : This paper assesses the degree to which the Libby Lobbying Model (LLM) describes the lobbying practices of advocacy groups in Israel. We conclude that the model is useful in describing advocacy activities in Israel, yet deviations from the model are evident as well. We propose that Israeli organisations could usefully adopt a modified version of the LLM, adapted to their own specific conditions, in order to strengthen the planning and evaluation of their lobbying activity.